Diseño De Zanjdora Para Prepracion De Terreno En El Cultivo De Flores Para La Empresa Flexport - Mora Prieto, Wilfran Stif (Universidad Antonio Nariño, 2024)
This paper presents the proposal for the design of a trencher for the Flexport company in Colombia. In the flower production process, the construction and cleaning of “beds” of (30 cm × 60 cm × 60 m) is required. Annually, the construction and cleaning process adds up to around 6,000 beds a year, which are currently prepared manually, generating a high cost of man-hours of work for the company.